PRINCIPLE OF MUTUAL CONSIDERATION IN SUNDANESE CULTURE (An Analysis on Sundanese Puppet Show entitled Kitab Sastra Jendra Rahayu Ningrat by Asep Sunandar Sunarya) - Rissa San Rizqiya (Eltin Journal : Journal of English Language Teaching in Indonesia, 2017)
Politeness is defined as language use or communication in order to avoid humiliation of both speaker and hearer. Deference refers to the use of language to show respect after considering aspects that urge the speaker to do so. The goal of deference is to satisfy the hearer (facesatisfying act). Deference and politeness are sometimes mixed up between one another (Aziz, 2008). The Principle of Mutual Consideration is offered by Aziz (2008)to complete the existing politeness theory. It is based on the causality law, which means a speaker should consider the result that may occur that is caused by her/his utterance.This article investigated politeness through the Principle of Mutual Consideration on puppet show entitled Kitab Sastra Jendra Rahayu Ningrat by puppet master Asep Sunandar Sunarya. The result shows that Sundanese shows politeness through the terms of addressee and the undak-usuk basa (deference). However, since it is a performing art, harm potentials is frequently and most obviously occurred.Keywords: politeness, face, Principle of Mutual Consideration